Real-world comparison of the efficacy of first-line therapies and the influence of risk factors in advanced renal cell carcinoma - Maximilian Haack; Stephanie Neuberger; Jan Hendrik Boerner; Stefanie Ziewers; Gregor Duwe; Robert Dotzauer; Axel Haferkamp; Rene Mager (Discover Oncology)
Abstract Introduction Systemic therapy for advanced renal cell carcinoma (aRCC) has become increasingly diverse. In the 1st-line setting, various combination therapies are available, with little comparative data on the efficacy of the therapies. The aim of this study was to compare the current 1st-line combination therapies under real-life conditions and to investigate risk factors in the patient population. Methods Patients with aRCC who started 1st-line IO/IO or IO/TKI combination  therapy between 03/2019 and 10/2023 were included. The primary endpoints were progression-free survival (PFS) and overall survival (OS). Secondary endpoints were time on treatment (ToT), duration of response (DoR), subsequent therapies, the evaluation of risk factors and their influence on PFS and OS. Survival data were analysed using Kaplan–Meier estimates with log-rank tests, risk factors for PFS and OS using Cox regression analysis. Results A total of 59 patients, mainly men (79.7%) with a median age of 64.8 years were included. The median follow-up was 21 months. The comparison of IO/IO vs. IO/TKI demonstrated a median PFS of 6 (2.08–9.92) vs. 14 (9.06–18.94) months (47 events; HR IO/TKI vs. IO/IO: 0.53 (0.29–0.99); p = 0.039) and a median OS of 20 (15.07–24.94) vs. 33 (21.68–44.32) months (32 deaths; HR IO/TKI vs. IO/IO: 0.74 (0.36–1.51); p = 0.403). Off all risk factors analysed only synchronous metastases proved to be of independent predictive value for PFS (HR 2.38; 95% CI 1.11–5.11; p = 0.026) and OS (HR 3.47; 95% CI 1.15–10.44; p = 0.027). Conclusion An IO/TKI therapy showed a significantly improved PFS in the real-world setting compared to an IO/IO combination. In terms of OS, the improved treatment response of the IO/TKI group did not prevail.